SOLAR POWER INTEGRATED GREEN CAMPUS FRAMEWORK FOR ELECTRIC VEHICLE CHARGING INFRASTRUCTURE - S.Brindha; V. Sri Priya (International Journal of Advanced Science and Computer Applications, 2026)
Global warming presents a serious threat to the environment and human livelihoods, with the residential building and transportation sectors being major contributors to greenhouse gas emissions. Electric vehicles (EVs) have gained prominence as a sustainable alternative to traditional fossil fuel-powered vehicles. The success of EVs hinges on efficient charging infrastructure. This research focuses on transportation pollution and greenhouse gas emissions, emphasizing the role of EVs. The study explores the importance of Electric Vehicle Charging Station (EVCS) location selection and introduces the concept of a Green Campus (GC) approach to enhance sustainability. As the world phases out carbon-producing vehicles like trains and buses, electrified transportation offers a greener alternative. However, to support the growing adoption of electric vehicles, charging infrastructure must expand and become more seamless. Some entities are exploring solar panels to power EVs, reducing their carbon footprint. The study proposes an EVSC-GC service architecture that aims to minimize carbon dioxide emissions, reduce electricity costs, and enhance charging efficiency. It leverages telematics, digital systems, and roadside cameras to optimize fuel consumption. Additionally, electronic wallets facilitate convenient payment for charging costs. This suggested EVSC-GC model improves charging demand, charging time, time distribution, and traveling velocity compared to existing methods, making electric mobility more sustainable and efficient.